2005
DOI: 10.1103/physrevlett.95.236601
|View full text |Cite
|
Sign up to set email alerts
|

Space-Charge-Limited Current Fluctuations in Organic Semiconductors

Abstract: Low-frequency current fluctuations are investigated over a bias range covering Ohmic, trap-filling, and space-charge-limited current regimes in polycrystalline polyacenes. The relative current noise power spectral density S(f) is constant in the Ohmic region, steeply increases at the trap-filling transition region, and decreases in the space-charge-limited-current region. The noise peak at the trap-filling transition is accounted for within a continuum percolation model. As the quasi-Fermi level crosses the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 41 publications
1
146
1
Order By: Relevance
“…(1) which can be observed experimentally (Carbone et al, 2005;Laha & Krupanidhi, 2002;Suh et al, 2000), and can be derived theoretically (Coelho, 1979) ε > 0 be both independent of the position x from the electrode where the electric current flows into the dielectric sample. The flow direction of the electric current is then given by the positive direction of x.…”
Section: J~vmentioning
confidence: 98%
See 3 more Smart Citations
“…(1) which can be observed experimentally (Carbone et al, 2005;Laha & Krupanidhi, 2002;Suh et al, 2000), and can be derived theoretically (Coelho, 1979) ε > 0 be both independent of the position x from the electrode where the electric current flows into the dielectric sample. The flow direction of the electric current is then given by the positive direction of x.…”
Section: J~vmentioning
confidence: 98%
“…SCLC. Here, we have deliberately aborted the assumption of a perfectly insulating ferroelectric film, as adopted by some other schools of thought (Alpay et al, 2003;Mantese & Alpay, 2005;Okatan et al, 2010), because experimental observations of small but finite leakage currents, as well as of SCLC currents, have been widely reported in the literature for ferroelectrics and other solid dielectrics (Bouregba et al, 2003;Carbone et al, 2005;Coelho, 1979;Laha & Krupanidhi, 2002;Pope & Swemberg, 1998;Poullain et al, 2002;Suh et al, 2000) and they form a subject of their own (Pope & Swemberg, 1998). For our consideration of SCLC in compositionally graded ferroelectric films, the MottGurney law J ~ V 2 does not apply, due to the following reasons: (i) In the case of a timevarying applied voltage, there is also the presence of displacement currents so that the conduction current J , which now does not necessarily equal the total current, could be varying with position, i.e.…”
Section: Polarization Offsets In Graded Ferroelectrics and The Need Fmentioning
confidence: 99%
See 2 more Smart Citations
“…9 For instance, application of lowfrequency noise spectroscopy to high-temperature superconducting YBa 2 Cu 3 O 7 films enabled their characterization, determination of fluctuation sources 10 and nonthermal properties; 11 in organic semiconductors low-frequency current fluctuations provide deep insight on trapping-detrapping processes and their characteristic times as well as peculiarities in voltage-driven transition from Ohmic to insulating phase in space-charge-limited conditions. 12 Investigation of noise properties plays a key-role also in development of semiconductor nanostructures-based devices. For example, it is found that photocurrent noise power in photodetectors can be directly related to the carrier density and to photogeneration level, their features can be affected by potential-barrier fluctuations; 13 it is demonstrated that noise gain and photoconductive gain are related in quantum well infrared photodetectors (QWIPs), 14 and inhomogeneous charge distribution in a quantum well (QWs) structure alters intensity and frequency dependence of noise power spectrum.…”
Section: Introductionmentioning
confidence: 99%